2014
DOI: 10.1016/j.visres.2014.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Posterior polymorphous corneal dystrophy 3 is associated with agenesis and hypoplasia of the corpus callosum

Abstract: Posterior polymorphous corneal dystrophy (PPCD) is a dominantly inherited disorder of the corneal endothelium that has been associated with mutations in the zinc-finger E-box binding homeobox 1 gene (ZEB1) gene in approximately one-third of affected families. While the corneal dystrophies have traditionally been considered isolated disorders of the corneal endothelium, we have recently identified two cases of maldevelopment of the corpus callosum in unrelated individuals with PPCD. The proband of the first fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Chromosome 10p11 deletion has not been reported previously in association with ACC and is not known to overlap any loci associated with syndromes including ACC as a feature (Bedeschi et al, ; Dobyns, ; Heide et al, ; Jang, Roldan, Frausto, & Aldave, ; Paul et al, ). In previous cases with cytogenetically visible chromosome 10p deletion containing p11.22, the patients were not reported to have ACC (Schinzel, ).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Chromosome 10p11 deletion has not been reported previously in association with ACC and is not known to overlap any loci associated with syndromes including ACC as a feature (Bedeschi et al, ; Dobyns, ; Heide et al, ; Jang, Roldan, Frausto, & Aldave, ; Paul et al, ). In previous cases with cytogenetically visible chromosome 10p deletion containing p11.22, the patients were not reported to have ACC (Schinzel, ).…”
Section: Discussionmentioning
confidence: 98%
“…In previous cases with cytogenetically visible chromosome 10p deletion containing p11.22, the patients were not reported to have ACC (Schinzel, ). Jang et al, () reported two unrelated cases with agenesis/hypoplasia of corpus callosum and PPCD3. Sequencing of ZEB1 identified frameshift mutations in the gene in both probands (Jang et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonocular phenotypes, associated with ZEB1 mutations have been reported previously, most commonly the presence of hernia (Krafchak et al., ; Aldave et al., ; Lechner et al., ; Liskova et al., ; Jang et al., ). In this study, there was a self‐reported history of umbilical hernia in the twins from family C24, and umbilical hernia in the father of the proband from family B3.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with PPCD3 also have a higher rate of abdominal hernia compared to the normal population (Krafchak et al., ). In one study, maldevelopment of the corpus callosum was noted in two PPCD3 probands (Jang et al., ).…”
Section: Introductionmentioning
confidence: 99%